2015
DOI: 10.1007/s10804-015-9216-3
|View full text |Cite
|
Sign up to set email alerts
|

The Mediating Role of Romantic Desolation and Dating Anxiety in the Association Between Interpersonal Competence and Life Satisfaction Among Polish Young Adults

Abstract: This study investigates the role of romantic desolation on life satisfaction in young adulthood. Using data from a Polish sample of 330 (205 females and 125 males) young adults aged 20–30, who completed Polish versions of the Satisfaction With Life Scale, Dating Anxiety Scale, Interpersonal Competence Questionnaire-Revised, and Social and Emotional Loneliness Scale for Adults-Short Form, romantic desolation (romantic loneliness and lack of a romantic partner) and dating anxiety were tested as mediators of the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 43 publications
0
12
0
1
Order By: Relevance
“…Indeed, the development of romantic relationships is viewed as a central developmental task for young adults (Shulman and Connolly 2013). Young adults who are able to successfully establish and maintain positive intimate relationships tend to be more satisfied with their lives and better adjusted well into later life (e.g., Adamczyk and Segrin 2016; Roisman et al 2004). Beyond psychological adjustment, the experiences in young adult romantic relationships set the foundation for later relationship success and child caregiving quality after the transition to parenthood (Feinberg 2002; Fincham and Cui 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the development of romantic relationships is viewed as a central developmental task for young adults (Shulman and Connolly 2013). Young adults who are able to successfully establish and maintain positive intimate relationships tend to be more satisfied with their lives and better adjusted well into later life (e.g., Adamczyk and Segrin 2016; Roisman et al 2004). Beyond psychological adjustment, the experiences in young adult romantic relationships set the foundation for later relationship success and child caregiving quality after the transition to parenthood (Feinberg 2002; Fincham and Cui 2011).…”
Section: Introductionmentioning
confidence: 99%
“…In the study, it was determined that interpersonal competence significantly predicts life satisfaction. It is observed that studies supporting this finding (Adamczyk and Segrin, 2016;Shaving, Yakıcı, and Baltacı, 2020) were conducted in the literature. Interpersonal competence is an important variable in terms of an individual's adjustment and psychological well-being (Kim et al, 2008).…”
Section: Discussionmentioning
confidence: 67%
“…DFNE was assessed in this study by using the Fear of Negative Evaluation subscale of the Dating Anxiety Scale for Adolescents (DAS-A; Glickman & La Greca, 2004). The DAS-A, a measure of dating anxiety comprised of three subscales assessing pertinent dating and social-evaluative distress (i.e., Fear of Negative Evaluation, Social Distress-Dating, and Social Distress-Group), was initially designed to measure dating anxiety in individuals aged 15-18 years old, and researchers have demonstrated its validity in assessing dating anxiety in young adult populations ranging from 20 to 30 years of age (Adamczyk, 2015;Adamczyk & Segrin, 2016). Given the established appropriateness in using the DAS-A for young adults, the DAS-A, particularly its Fear of Negative Evaluation subscale, was considered to be suitable for measuring DFNE in target population range (i.e., graduate psychology students at least 18 years old).…”
Section: Methodsmentioning
confidence: 99%